Nth Power Lottery and Mimesis of the Future in Yom Kippur's Ceremonial Law, Hasidic Thought, and Early-Modern Folklore - Dickmann, Iddo (Heythrop journal, 2025)
In Nth power lottery, a lottery within a lottery, as envisioned by Deleuze, the frame, the pragmatic circumstances that surround the game (e.g., its rules), are also given to chance. I argue that both the ceremonial, Temple-based, Yom Kippur lottery in the Bible and Talmud, and the subsequent idea of Yom Kippur as a heavenly lot-casting day, as expressed in the Midrash, liturgy, Hasidic thought, and even folklore tales recounting games of chance during Yom Kippur, follow the Nth power paradigm. Reading these texts in light of this paradigm, and analysing this paradigm in light of the phenomenology of mise en abyme—a mimetic double at the heart of the imitatee—reveals a unique process-theology, where the act of repentance is mise en abyme of a radically absent imitatee—the ‘Before God’—and eventually an incarnation of it.